Catalyst-free formal [3 + 2] cycloaddition of stabilized N, N-cyclic azomethine imines to 3-nitrobenzofurans and 3-nitro-4H-chromenes: access to heteroannulated pyrazolo[1, 2-a]pyrazoles. Issue 46 (15th November 2021) - Osipov, Dmitry V.; Korzhenko, Kirill S.; Rashchepkina, Daria A.; Artemenko, Alina A.; Demidov, Oleg P.; Shiryaev, Vadim A.; Osyanin, Vitaly A.
Abstract : We have studied the [3 + 2]-cycloaddition of various N, N -cyclic azomethine imines to 3-nitrobenzofurans. Abstract : We have studied the [3 + 2]-cycloaddition of various N, N -cyclic azomethine imines to 3-nitrobenzofurans. This process is a rare example of their dearomatization. We have also extended this process to the related 3-nitro-4 H -chromenes as dipolarophiles. Both reactions provide access to benzofuro- and chromeno-condensed pyrazolo[1, 2- a ]pyrazoles with 100% atom economy in a diastereoselective manner under mild eco-friendly conditions. Finally, on the basis of DFT calculations, the mechanistic insights into the mentioned [3 + 2]-cycloadditions and explanations of the experimentally determined limitations of the method are given. Hirshfeld atomic charge values of push–pull heterocycles were suggested as a criterion for a priori assessment of the possibility of their dipolar cycloaddition with N, N -cyclic azomethine imines.